Exopolysaccharide-producing Lacticaseibacillus paracasei strains isolated from kefir as starter for functional dairy products - Bengoa, Ana Agustina; Dueñas, María Teresa; Prieto, Alicia; Garrote, Graciela L.; Abraham, Analía G. (Frontiers in Microbiology, 2023)
Exopolysaccharides (EPS) produced by lactic acid bacteria are molecules of great interest for the dairy food industry. Lacticaseibacillus paracasei CIDCA 8339, CIDCA 83123 and CIDCA 83124 are potentially probiotic strains isolated from kefir grains whose EPS-production on MRS broth is dependent on incubation temperature. The aim of the present work is to evaluate the effect of fermentation temperature on the characteristics of EPS produced in milk by L. paracasei strains and the consequent impact on the rheological properties of the fermented products. Additionally, the protective effect of these EPS against Salmonella infection was evaluated in vitro. Acid gels with each strain were obtained by milk fermentation at 20 °C, 30 °C and 37 °C evidencing for all the strains a reduction in growth and acidification rate at lower temperature. L. paracasei CIDCA 83123 showed low fermentation rate at all temperatures requiring between 3 and 7 days to obtain acids gels, whereas CIDCA 8339 and 83124 needed between 24-48 h even when the temperature was 20 °C. Fermentation temperature led to changes in crude EPS characteristics of the three strains, observing an increase in the relative amount of the high molecular weight fraction when the fermentation temperature diminished. Additionally, EPS83124 and EPS83123 presented modifications in monosaccharide composition, with a reduction of rhamnose and an increase of amino-sugars as temperature rise. These changes in the structure of EPS83124 resulted in an increase of the apparent viscosity of milks fermented at 20 °C (223 mPa.s) and 30 °C (217 mPa.s) with respect to acid gels obtained at 37 °C (167 mPa.s). In order to deepen the knowledge on EPS characteristics, monosaccharide composition of low and high molecular weight EPS fractions were evaluated. Finally, it was evidenced that the preincubation of intestinal epithelial cells Caco-2/TC-7 with EPS8339 and EPS83124 partially inhibit the association and invasion of Salmonella. In light of these results, it can be concluded that the selection of the EPS-producing strain along with the appropriate fermentation conditions could be an interesting strategy to improve the technological properties of these L. paracasei fermented milks with potential protective effects against intestinal pathogens.